The influence of the solid to plasma phase transition on the generation of plasma instabilities. Issue 1 (December 2017) - Kaselouris, E.; Dimitriou, V.; Fitilis, I.; Skoulakis, A.; Koundourakis, G.; Clark, E.; Bakarezos, Μ.; Nikolos, I.; Papadogiannis, N.; Tatarakis, M.
Abstract The study of plasma instabilities is a research topic with fundamental importance since for the majority of plasma applications they are unwanted and there is always the need for their suppression. The initiating physical processes that seed the generation of plasma instabilities are not well understood in all plasma geometries and initial states of matter. For most plasma instability studies, using linear or even nonlinear magnetohydrodynamics (MHD) theory, the most crucial step is to correctly choose the initial perturbations imposed either by a predefined perturbation, usually sinusoidal, or by randomly seed perturbations as initial conditions. Here, we demonstrate that the efficient study of the seeding mechanisms of plasma instabilities requires the incorporation of the intrinsic real physical characteristics of the solid target in an electro-thermo-mechanical multiphysics study. The present proof-of-principle study offers a perspective to the understanding of the seeding physical mechanisms in the generation of plasma instabilities. Exploring the plasma processes in the pre-plasma state that lead to instabilities is challenging. Here the authors probe the evolution of the plasma phase change and the instabilities in plasma created by an exploding copper wire in Z-pinch geometry using shadowgraphy.